Therapeutic Plasma Exchange in Immune-Mediated Thrombotic Thrombocytopenic Purpura: From Cornerstone to Contextualized Therapy - Fedai Özcan; Alexandra Brinkhoff; Ralph Wendt (Journal of Clinical Medicine, 2026)
Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a rare, life-threatening thrombotic microangiopathy caused by severe ADAMTS13 deficiency due to anti-ADAMTS13 autoantibodies. The resulting persistence of ultra-large von Willebrand factor (VWF) multimers promotes uncontrolled platelet adhesion and aggregation in the microcirculation, leading to thrombocytopenia, microangiopathic hemolytic anemia, and ischemic organ injury. Therapeutic plasma exchange (TPE) has transformed the prognosis of iTTP by removing circulating autoantibodies and replenishing functional ADAMTS13, and it remains a life-saving intervention in acute disease. However, TPE is invasive, resource-intensive, dependent on central venous access and plasma availability, and associated with catheter-related, hemodynamic, metabolic, infectious, and plasma-related adverse events. The therapeutic landscape has changed substantially with the incorporation of immunosuppression and the anti-VWF nanobody caplacizumab. Caplacizumab rapidly blocks VWF–platelet interactions at the effector level, whereas corticosteroids and B-cell-directed therapy target the autoimmune basis of iTTP. Triple therapy with TPE, immunosuppression, and caplacizumab accelerates platelet recovery and reduces unfavorable outcomes. At the same time, accumulating observational evidence and early prospective data suggest that selected patients may achieve remission with caplacizumab plus immunosuppression without routine first-line TPE. This perspective review critically re-evaluates the role of TPE in contemporary iTTP management. We propose that TPE should no longer be viewed exclusively as an obligatory universal first-line intervention, but rather as a contextualized component of individualized, response-adapted care. TPE remains indispensable for severe, unstable, or refractory disease and must be immediately available when TPE-free treatment is attempted. Safe implementation of TPE-free strategies requires experienced centers, rapid ADAMTS13 testing, immediate access to caplacizumab and immunosuppression, careful patient selection, and close clinical and laboratory monitoring. Defining which patients can be treated safely without TPE is a central challenge for future trials and guideline development.